2021
DOI: 10.3389/fmed.2021.642710
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Endothelial Function in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome–Results From Open-Label Cyclophosphamide Intervention Study

Abstract: Introduction: Patients with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) present with a range of symptoms including post-exertional malaise (PEM), orthostatic intolerance, and autonomic dysfunction. Dysfunction of the blood vessel endothelium could be an underlying biological mechanism, resulting in inability to fine-tune regulation of blood flow according to the metabolic demands of tissues. The objectives of the present study were to investigate endothelial function in ME/CFS patients compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 54 publications
6
29
0
Order By: Relevance
“…This is consistent with recent hypotheses describing vasoconstriction in muscle and brain as a principal element of ME/CFS ( 42 46 ), and findings of cerebral hypoperfusion ( 47 49 ) and intracranial hypertension ( 50 ) in ME/CFS patients. It is also consistent with studies that have shown that endothelial function is impaired in ME/CFS ( 51 , 52 ), both in large vessels and in the microcirculation ( 53 , 54 )—associated with redox imbalance ( 51 ). Finally, it is consistent with a new hypothesis for ME/CFS which suggests that endothelial senescence underpins ME/CFS by disrupting the intestinal barriers and BBBs ( 55 ), as well as with suggestions that leakage from dysfunctional blood vessels could explain many of the symptoms in ME/CFS ( 56 ).…”
Section: Pathophysiological Mechanismssupporting
confidence: 91%
“…This is consistent with recent hypotheses describing vasoconstriction in muscle and brain as a principal element of ME/CFS ( 42 46 ), and findings of cerebral hypoperfusion ( 47 49 ) and intracranial hypertension ( 50 ) in ME/CFS patients. It is also consistent with studies that have shown that endothelial function is impaired in ME/CFS ( 51 , 52 ), both in large vessels and in the microcirculation ( 53 , 54 )—associated with redox imbalance ( 51 ). Finally, it is consistent with a new hypothesis for ME/CFS which suggests that endothelial senescence underpins ME/CFS by disrupting the intestinal barriers and BBBs ( 55 ), as well as with suggestions that leakage from dysfunctional blood vessels could explain many of the symptoms in ME/CFS ( 56 ).…”
Section: Pathophysiological Mechanismssupporting
confidence: 91%
“…An autoantibody-mediated mechanism may influence, indirectly or directly, the fine-tuned autoregulation of blood flow required to meet the metabolic demands of tissues. Endothelial dysfunction has been shown in patients with ME/CFS (65,66), and this was also supported in substudies linked to the CycloME and RituxME trials (67). The reduced levels of certain arachidonic acid derivatives seen in the present study may impact the vascular tone and blood flow (68).…”
Section: Discussionsupporting
confidence: 77%
“…In our previous study of 35 ME/CFS patients, peripheral ED assessed by RH-PAT was observed in half of the patients and was associated with disease severity [ 9 ]. A recent study of postinfectious ME/CFS confirmed these findings by demonstrating ED through both RH assessment and flow-mediated dilatation [ 11 ]. ED resulting in muscle and cerebral hypoperfusion are considered key pathomechanisms in ME/CFS [ 7 , 12 , 42 ].…”
Section: Discussionmentioning
confidence: 74%